Beyond Ethics: Exploring the Indirect Effect of Subordinate Extraversion and Agreeableness on Sustainable Performance and Moderating Role of Psychological Diversity Climate - Altaf Akbar (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The study aims to explore sustainable performance antecedents and the moderating and mediating variables in such associations. This study is to explore the relationship between ethical leadership and sustainable performance, with the moderating influence of psychological diversity climate and the mediating function of agreeableness and subordinate extroversion. Methodology: This study focused on the SMEs located in Lisbon and Porto regions, and information was gathered from 310 middle and senior managers employed by SMEs. These answers were examined through the use of moment structure analysis technique. Findings: The SPSS 24 and Smart PLS 4 were used for statistical analysis and findings showed that subordinate extroversion and agreeableness have a major mediating effect between sustainable performance and ethical leadership. Furthermore, the association between subordinate extroversion and agreeableness and sustainable performance is strongly moderated by psychological diversity climate. Implications/Novel Contribution: Middle and senior managers of SMEs can naturally reach the highest level of sustainability if they emphasize agreeableness and extroversion and adhere to the ethical leadership strategy. Its impact on subordinate extroversion, agreeableness, and eventually sustained performance is highlighted. Additionally, psychological diversity climate moderated the relationship between ethical leadership and sustainable performance. Study brings key practical and policy insights for scholars’ researchers and social sciences researchers as well as policy makers.